1990
DOI: 10.1159/000247927
|View full text |Cite
|
Sign up to set email alerts
|

Ciclosporin in Localized and Systemic Scleroderma – A Clinical Study

Abstract: Four patients with systemic scleroderma and 1 patient with localized scleroderma were treated with ciclosporin (CS) given in daily doses between 2.2 and 5.6 mg/kg body weight for 3–26 months. Under this medication clinical improvement was observed in 4 patients with partial regression of cutaneous sclerosis and inflammation, healing of fingertip ulcerations or leg ulcers and improvement of articular mobility. However, in 1 patient with rapidly advancing systemic scleroderma a short-term therapy with CS in low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
(7 reference statements)
0
13
0
Order By: Relevance
“…Agents which have been used in the treatment of this disorder include corticosteroids, non-steroidal anti-inflammatory drugs, vitamin E, penicillamine, and cyclosporin (1,2). However, there has been no really satisfactory treatment for this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Agents which have been used in the treatment of this disorder include corticosteroids, non-steroidal anti-inflammatory drugs, vitamin E, penicillamine, and cyclosporin (1,2). However, there has been no really satisfactory treatment for this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Ciclosporin is a fungal metabolite with potent immunosuppressive activity, affecting both humoral and cell‐mediated immunity. It has been shown to be effective in the treatment of SSc 6 as well as disabling morphoea 7 . Several authors felt that the response to ciclosporin in their patients with SSc was more obvious in the sclerosis of the skin than in the systemic involvement 8 .…”
mentioning
confidence: 99%
“… 24 Finally, 27 review articles were excluded, and the remaining 37 identified primary research articles were included into the analysis. 24 60 The 37 articles consisted of 19 case reports, 15 case series, 1 open-label, randomized controlled trial with a no-treatment arm (group I iloprost vs group II iloprost with low-dose CsA), one open-label, prospective study with a historical control group (CSA group vs historical placebo group of the chlorambucil trial), 61 and one retrospective study without control (patients received prednisolone (0.5 mg/kg/d) and tacrolimus; Table 1 ).…”
Section: Results Of the Systematic Literature Searchmentioning
confidence: 99%